Ijarah Muntahiah Bittamlik (IMBT): Capital Strategy, Participation Opportunities, and Implementation of Close Loop Economy in The Hospital - Fadjar Setiyo Anggraeni (International ABEC, 2022)
This paper aims to uncover and provide solutions to capital problems that often occur in organizations, especially small and medium-sized (and private) hospitals. Limited financial resources have become a major problem for many hospitals that are developing to increase the utility of services. Using qualitative methods with the type of case study research, this paper provides a comprehensive description of the sources of capital, governance, and rental value as well as the profit sharing of a simulated investment. The results of this study reveal that IMBT can be a capital strategy for service development plans in hospitals.